Evaluation of Electrical Submersible Pump (ESP) Based on Energy Loss Analysis At South-Eeast Sumatra (SES) Block - Andika Rizky Febrianto; Suranto; KRT Nur Suhascaryo; Muhammad Nauval Rizki; Riko Meidiya Putra; Slamet Kurniansyah (Journal of Petroleum and Geothermal Technology, 2026)
The production wells in the South-East Sumatra (SES) Block are characterized as a mature field with a high water cut, requiring significant energy to lift fluids to the surface. The main challenge faced is the high energy inefficiency of the Electrical Submersible Pump (ESP). Therefore, this study aims to evaluate ESP performance based on energy loss analysis, determine the best optimization scenario to reduce energy requirements, and analyze potential operational cost savings. The research method involves evaluating the distribution of energy losses in hydraulic components (friction, backpressure, and pumps) and electrical components (motor, cables, and surface equipment). Based on this evaluation, three optimization scenarios were conducted: backpressure loss, frictional loss, and pump loss. Furthermore, a cost savings analysis is carried out by comparing the costs before and after optimization. The results indicate that energy inefficiency in high flow rates wells is dominated by backpressure and friction, while in relatively small flow rates wells is caused by low pump efficiency and backpressure. The application of the best optimization scenario in the five wells can reduce the total energy requirement from 768.83 kW to 568.21 kW. This resulted in a cost reduction from US$512,641 to US$378,869.